Highly heterogeneous upper-mantle structure in Fennoscandia from finite-frequency P-body-wave tomography. Issue 2 (17th March 2022) - Bulut, N; Thybo, H; Maupin, V
SUMMARY: We present a P -wave velocity model of the upper mantle, obtained from finite-frequency body-wave tomography, to analyse the relationship between deep and surface structures in Fennoscandia, one of the most studied cratons on the Earth. The large array aperture of 2000 km × 800 km allows us to image the velocity structure to 800 km depth at very high resolution. The velocity structure provides background for understanding the mechanisms responsible for the enigmatic and strongly debated high topography in the Scandinavian mountain range far from any plate boundary. Our model shows exceptionally strong velocity anomalies with changes by up to 6 per cent on a 200 km scale. We propose that a strong negative velocity anomaly down to 200 km depth along all of Norway provides isostatic support to the enigmatic topography, as we observe a linear correlation between hypsometry and uppermost mantle velocity anomalies to 150 km depth in central Fennoscandia. The model reveals a low-velocity anomaly below the mountains underlain by positive velocity anomalies, which we explain by preserved original Svecofennian and Archaean mantle below the Caledonian/Sveconorwegian deformed parts of Fennoscandia. Strong positive velocity anomalies to around 200 km depth around the southern Bothnian Bay and the Baltic Sea may be associated with pristine lithosphere of the present central and southern Fennoscandian craton that has been protected from modification since its formation. However, the Archaean domain in the north and the marginal parts of the Svecofennian domains appear to have experienced strong modification of the upper mantle. A pronounced north-dipping positive velocity anomaly in the southern Baltic Sea extends below Moho. It coincides in location and dip with a similar north-dipping structure in the crust and uppermost mantle to 80 km depth observed from high-resolution, controlled source seismic data. We interpret this feature as the image of a Palaeoproterozoic boundary that has been preserved for 1.8 Gy in the lithosphere.